Single-crystalline organic one-dimensional microarrays toward high-performing phototransistors - Deng, Xin (2022)
Organic phototransistors (OPTs) with the ability to convert light signals into electrical signals have drawn attention for a variety of potential multifunctional applications, such as images, night vision, and optical communications, because of their advantages including designable molecular structures and low-cost and large-area fabrication. However, the performances of OPTs are hampered by organic semiconducting architectures with low crystallinity, random crystallographic orientation, and stochastic position arising from the uncontrollable dewetting dynamics, which is detrimental to the transport of carriers and separation of excitons. In this work, a capillary-bridge lithography strategy to fabricate 1D single-crystal arrays with the feature of high crystallinity, strict alignment, and accurate positioning is utilized. Owing to the application periodical micropillars of the template with asymmetric wettability, capillary bridges with unidirectional dewetting behavior are achieved to fabricate large-area single-crystalline arrays with precise alignment and pure crystallographic orientation. As a result, encouraged by the high hole mobility of 13.52 cm2 V−1 s−1, high-performance OPTs with photosensitivity up to 2.5 × 107, responsivity up to 8.8 × 104 A W−1, and specific detectivity up to 7.5 × 1015 Jones are constructed. This research provides a guide for patterning large-area 1D single-crystalline arrays toward various high-performance multifunctional optoelectronic devices.